Social Change in Conflict-Affected Areas of Nepal - World Bank (Washington, DC, 2012)
This note reports on the findings of a recent study to assess social change in conflict areas of Nepal. It looks specifically at the impact on hierarchical relations based on gender, caste, and ethnicity. All parts of society have been affected by positive, and negative social changes. Most of the positive changes have not yet become imbedded in the fabric of social relations, but are enforced through coercion, and the threat of violence. The challenge for development actors will be to capitalize on these positive changes, and effectively address problems of exclusion and social inequality.